Impact of low-intensity isocapnic hyperpnoea on blood lactate disappearance after exhaustive arm exercise. Issue 9 (14th May 2007) - Perret, Claudio; Mueller, Gabi
Abstract : Objective: To investigate the impact of low-intensity isocapnic hyperpnoea (IH) on blood lactate disappearance after exhaustive arm exercise in comparison with passive and active recovery using the previously loaded muscle group. Design: Randomised, crossover trial. Setting: Institute for Sports Medicine. Participants: 18 healthy non-smoking and physically active male subjects. Interventions: Subjects performed three arm cranking tests to volitional exhaustion on 3 different days at least 48 h apart. Arm exercise was randomly followed by 30 min of passive recovery (PR), active arm cranking (AC) at 30% of peak power output or ventilatory recovery (VR) by means of IH at 30% of 12 s maximal voluntary ventilation. Blood lactate concentrations were measured every 2 min during recovery. Main outcome measurements: Blood lactate disappearance during the three different recovery strategies. Results: No significant differences in blood lactate concentrations were found between interventions PR, AC and VR during the whole measurement period. Mean (SD) peak lactate concentrations were 11.09 (1.98) mmol/l for PR, 11.13 (1.44) mmol/l for AC and 11.25 (1.93) mmol/l for VR. At the end of the recovery period measured lactate concentrations were 4.35 (1.56) mmol/l for PR, 3.77 (1.60) mmol/l for AC and 4.09 (1.35) mmol/l for VR. Moreover, all other variables measured were not significantly different, with the exception of higher average recovery heart rates during AC (116 (9) bpm) and VR (111 (17) bpm) compared with PR (93 (11) bpm). Conclusion: Low-intensity IH seems not to enhance blood lactate disappearance after exhaustive arm exercise compared with passive or active recovery using the previously loaded muscle group. The magnitude of the involved muscle mass appears critical to effective active recovery.